An artificial neural network-source apportionment-based prediction model for carbon monoxide from total number of ships calling by ports in Malaysia - Shazlyn Milleana Shaharudin (Tanjung Malim, 2024)
An artificial neural network-source apportionment-based prediction model for carbon monoxide from total number of ships calling by ports in Malaysia by Shazlyn Milleana Shaharudin